Locke’s Diagnosis of Akrasia - Matthew A. Leisinger (Journal of Modern Philosophy)
I argue for a new interpretation of Locke’s account of akrasia. On this interpretation, akrasia occurs on Locke’s account because certain cognitive biases endemic to the human mind dispose us to privilege present over future happiness. As a result, we end up irrationally pursuing present pleasure and the removal of present pain even as we simultaneously judge that doing so runs contrary to our own greater good. In this sense, I argue that Locke seeks to diagnose akrasia by identifying its underlying psychological causes.